Crime, law and society in Nigeria: essays in honour of Stephen Ellis - Akinyele, Rufus; Dietz, Ton; Ellis, Stephen (Afrika-Studiecentrum series, 2019)
Front Matter -- Copyright Page -- Acknowledgements -- Notes on Contributors -- Introduction /Rufus Akinyele and Ton Dietz -- Stephen Ellis: His Life and Work /Gerrie Haar -- Theft in Early Colonial Lagos, 1861–1906 /Paul Osifodunrin -- Smuggling across the Nigeria: Benin Border and Its Impact on Nigeria’s Economic Development /Jackson A. Aluede -- Changing Patterns of Crime and Malfeasance in Nigerian Port Environments since the 1990s /Edmund Chilaka -- Nature and Management of Human Trafficking: The Nigerian Edo People’s Experience /Leo Enahoro Otoide -- Militancy and Criminality in the Niger Delta Region of Nigeria /Abiodun Oluwadare -- Crime at the University of Lagos: Insights from Akoka Campus /Franca Attoh -- Reporting Crime in Contemporary Lagos /Samson Folarin -- Currency Counterfeiting and “Substantial Justice” in Colonial Nigeria: Rex vs Tijani Ali, 1931–33 /Ayodeji Olukoju -- Class Based Criminal Justice Regime, Supermarket Courts, and Illicit Interests: The Nigerian Criminal Justice Administration System in Critical Perspective /A.E. Akintayo -- Stephen Ellis, (2016) This Present Darkness: A History of Nigerian Organised Crime. London: Hurst and Company /Ayodele Atsenuwa -- Back Matter -- Short CV Stephen Ellis -- Books -- Index.